2017
DOI: 10.1055/s-0036-1597949
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Nasal Reconstruction

Abstract: The rise in cutaneous malignancies over the past 20 years has led to significant advances in reconstructing the nose from an aesthetic and functional standpoint. The principles of nasal reconstruction center on application of the nasal subunit principle, three-layered reconstruction, nasal skin characteristics, and patient factors. Reconstructive planning starts with proper defect analysis, followed by application of the reconstructive ladder for soft-tissue repair, adequate structural support, and repair of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Surgical techniques have also evolved and various methods are currently available as a result of the continuing search for a comprehensive surgical technique. Our current report is no exception [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 90%
“…Surgical techniques have also evolved and various methods are currently available as a result of the continuing search for a comprehensive surgical technique. Our current report is no exception [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 90%
“…It was as well treasured by our Chinese counterparts because the costal cartilage was satisfying in both quantity and quality, particularly when a large cartilaginous defect occurred 7,47 . The intrinsic curve and suppleness of conchal cartilage make it the first choice to design alar batten grafts or replace lateral cartilage, while the prominent stiffness and abundance of costal cartilage are ideal to play the role as a central support element or dorsal onlay graft [48][49][50] . Sannier et al 51 also preferred to use ipsilateral conchal bowl cartilage and suggested the exploitation of costochondral cartilage when cartilage was in great demand.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in reconstructing nasal subunits lies in their contour, skin texture, and the limited availability of adjacent skin. Using a skin graft often results in an aesthetically poor result, with problems including differences in skin texture and a depression scar [6]. The use of dorsal nasal flaps for nasal dorsum or supra-tip reconstruction is not innovative.…”
Section: Discussionmentioning
confidence: 99%